Lysozyme immobilized on chitosan beads: Kinetic characterization and antimicrobial activity in white wines. (May 2016) - Liburdi, K.; Benucci, I.; Palumbo, F.; Esti, M.
Abstract: In order to be able to use lysozyme as an anti-microbial agent during the winemaking process, hen egg-white lysozyme (HEWL) was covalently immobilized on chitosan beads. A cell suspension of Oenococcus oeni, an enological strain involved in the winemaking process, was utilized as enzyme substrate. Both a kinetic study and evaluation of antibacterial activity, of the free and immobilized HEWL, were performed in model and real white wines. The catalytic parameters Vmax and kcat turned out to be higher for free-HEWL in model and white wines, demonstrating that covalent immobilization affected cell lysis velocity. However the Km values were similar for the free and immobilized enzyme in wine model and only slightly lower in white wines for the immobilized biocatalyst. Moreover, the covalent immobilization also reduced the lysozyme antimicrobial efficiency, although it is worth noting that, in white wine, the antimicrobial activity of immobilized HEWL is not affected by the concentrations of free SO2 and total phenols. Even though the proposed covalent immobilization strongly affected the lysozyme catalytic and antimicrobial efficiency, it improved the stability of immobilized HEWL in white wine, thus demonstrating its potential for use as an efficient antimicrobial agent in wine-making applications. Highlights: Catalytic and antimicrobial efficiency of lysozyme, covalently immobilized on chitosan beads, was tested in white wines. The covalent immobilization of lysozyme caused the loss of its catalytic and antimicrobial efficiency. The antimicrobial activity of immobilized biocatalyst, in white wines, is not affected by the wine inhibitors.